Pendidikan Karakter dalam Perspektif Pendidikan Islam - Muhammad Fathurrohman (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2016)
Character education is the deliberate effort (conscious) to help people understand, care about, and implement core ethical values. Expectations character and personality are formed in self-learners that is the dream of success of character education. Learners are expected to understand the values imparted to him, entirely without any mis-understanding at all. Even learners will be expected to understand the development of these values. Koran which is the main source of Islamic education, a lot of mention about character education, but with an expression of character, almost every story contained in the Koran, in which there is character education.